Pengaruh Variasi Konsentrasi Surfaktan Iselux Ultra Mild pada Formulasi Hydrating Facial Wash Potassium Azeloyl Diglycinate - Rohmani, Sholichah; Ningrum, Sonia Karunia; Wardhani, Wening Dyah; Kundarto, Wisnu (Jurnal Kefarmasian Indonesia, 2022)
Potassium Azeloyl Diglycinate is an innovative molecule that active as a skin hydrating, brightening agent, and treating skin hyperpigmentation. Facial Wash with foam stabilizing agents called surfactants is a facial cleansing soap that used daily to clean dirt and oil on the face. Iselux ultra mild surfactant as a mild surfactant has a low irritation profile, stable to pH and has a soft and abundant foam. This research is an experimental study. Formulating a good Hydrating Facial Wash Potassium azeloyl diglycinate with the addition of of Iselux ultra mild surfactants in various concentration, according to physical and chemical characteristics as well as a facial wash hydration test. Researchers used various concentration of 28: 30: 32% Iselux Ultra Mild for 3 types of formulas. The test results were analyzed by one way ANOVA. The results of testing the characteristics of physical and chemical properties including organoleptic tests, homogeneity, spreadability, foam height, viscosity, and pH as well as hydration evaluation showed that the facial wash was not change during storage for 12 days using the cycling test method. Formula 3 with the highest surfactant concentration met the best qualification on the parameters compared to Formula 1 and Formula 2. The hydration activity test based on the results of the pre and post test showed that the Facial Wash Potassium azeloyl diglycinate had moisturizing activity on the face.